Spain's realistic potential for ocean alkalinity enhancement: Carbon dioxide removal through industrial integration - Spyros Foteinis; James Campbell; Mohammad Madankan; Liam Adam Bullock; Jose Maria Valenzuela; Javier Lezaun; Mijndert van der Spek; Phil Renforth (Journal of Cleaner Production, 2026)

Comparative life cycle assessment of CO2 removal solutions, including ocean liming, based on different energy sources and carbon storage methods - Francesco Campo; Giovanni Dolci; Mario Grosso; Phil Renforth; Mijndert van der Spek; Spyros Foteinis; Marta Manca Zeichen; Roberto Borghesi; Stefano Caserini (International Journal of Greenhouse Gas Control, 2026)

Guidance on integrating marine environmental impacts of ocean alkalinity enhancement into life cycle assessment - Mona H. Delval; Patrik J. G. Henriksson; Paul Behrens; Laura Scherer; Pablo Trucco-Pignata; Patricia Grasse; Phil Renforth; Nils Thonemann (The International Journal of Life Cycle Assessment, 2026)
Purpose Ocean alkalinity enhancement (OAE) is considered a promising marine carbon dioxide removal (mCDR) option and may contribute to climate change mitigation. Life cycle assessment (LCA) is used to assess OAE environmentally but faces limitations in capturing marine impacts. Improving the assessment of OAE in LCA requires a detailed understanding of its marine environment impact pathways to develop sub-compartmentalised and regionalised characterisation factors (CFs). We demonstrate how such pathways can be identified. Methods We build on Woods et al. (2021), who propose a qualitative framework to identify key components of impact pathways, and Richter et al. (2024), who provide guidance on framework development in a multidisciplinary context. We develop a methodological approach that allows to qualitatively identify the marine environmental impact pathways of OAE and determine which components are integrated in LCIA models or missing, as an initial phase toward developing CFs for life cycle impact assessment (LCIA). Results and discussion Our methodological approach includes: (1) the selection of literature on OAE and its impacts on marine ecosystems; (2) the identification of the marine elementary flows in the life cycle inventory and the fate, exposure, and effect processes; (3) the inputs from LCIA, oceanography, and technology experts; (4) the review of LCIA models to examine which elements of the marine environmental impact pathways are represented or lacking; (5) the definition of research priorities to advance the assessment of OAE’s environmental impacts within LCA. We identified three impact categories associated with OAE marine environmental impacts pathways: marine ecotoxicity, marine eutrophication, and ocean acidification. Existing LCIA models only partially capture these pathways and require adaptation for assessing comprehensively OAE. Research priorities include conducting additional experiments on the ecotoxicological and eutrophic effects of OAE deployment in marine environments, and the effect of added alkalinity on a broader range of marine calcifiers. Several of our recommendations are also relevant to enhance marine technologies’ assessments in LCA more broadly, such as improving the ocean’s representation in models, modelling direct release to offshore marine waters, and broadening the elementary flows’ coverage for marine eutrophication. Conclusion We present a methodology to identify marine environmental impact pathways of OAE, providing a first phase toward developing CFs. The methodological approach might be adapted to other marine technologies, where identifying impact pathways require a multidisciplinary approach that combines the LCA field with oceanography and engineering expertise.

Assessment of solid ikaite release into seawater – implications for ocean alkalinity enhancement - Stefan Baltruschat; Jens Hartmann; Niels Suitner; Charly A. Moras; Carl Lim; Laura Bastianini; Phil Renforth (Applied Geochemistry, 2026)

Atmospheric carbon dioxide removal using layers of lime - Olivia Hawrot; Phil Renforth (Science of The Total Environment, 2025)

An inventory of UK mineral resources suitable for enhanced rock weathering - Mohammad Madankan; Phil Renforth (International Journal of Greenhouse Gas Control, 2023)

The potential environmental response to increasing ocean alkalinity for negative emissions - Sarah Gore; Phil Renforth; Rupert Perkins (Mitigation and Adaptation Strategies for Global Change, 2019)